Two-Dimensional Parametric Study of an Embankment on Clay Improved by an Artificial Crust Composite Foundation - Ying Wang; Zhenhua Hu; Yonghui Chen; Hongtian Xiao (Advances in Civil Engineering)
In order to reduce the foundation settlement, conserve resources, and be environmental-friendly while increasing the use of soil resources, an artificial crust layer formed by in situ stabilization is proposed to combine with prestressed pipe piles over soft ground in road construction. In this study, a centrifuge test and two-dimensional coupled-consolidation finite-element analyses are conducted to simulate the construction of an embankment. And a two-dimensional parametric study is conducted to study the performance indicated by maximum long-term settlement, excess pore water, and tensile stress under various conditions. The results of the centrifuge test clearly show that the measured settlement, excess pore water, and tensile stress are in good agreement with the calculated results. In addition, the key factors of pile spacing and thickness and strength of the crust have an influence on the maximum settlement, stress of the foundation, and tensile stress of the crust using the two-dimensional coupled-consolidation finite-element analyses. And the stress transfer regular of the foundation is analyzed under various conditions. Moreover, the failure of the crust contained tensile cracking and shearing failure and the thickness of the pile that pierced the crust are also affected by the key factors.